Description of a new Eratigena Bolzern, Burckhardt & Hänggi, 2013 (Arachnida: Araneae: Agelenidae) from the Balkans based on an integrative approach - Geci, Donard; Ibrahimi, Halil; Naumova, Maria; Bilalli, Astrit; Koblmüller, Stephan; Musliu, Milaim; Grapci-Kotori, Linda; Gashi, Agim; Schäffer, Sylvia; Wagner, Maximilian (Zootaxa, 2025)
New data on agelenid spiders of the Balkans are provided. A new species of the genus Eratigena Bolzern, Burckhardt & Hänggi, 2013, Eratigena mirusha sp. nov. (♂/♀) from the Koznik Mountain in Kosovo is described, based on molecular and morphological data. The males Eratigena mirusha sp. nov. are most similar to E. agrestis (Walckenaer) but possess differently shaped conductor and retrolateral tibial apophysis. Females of both species differ in the shape of the epigyne and the posterior sclerite and from the positions of the copulatory openings, and the epigynal pseudo teeth. The genetic divergence calculated based on the barcode region of the cytochrome c oxidase subunit I gene (COI) confirms the morphological distinctness and supports Eratigena mirusha sp. nov. as a sister species of E. agrestis.